2015
DOI: 10.14419/ijbas.v4i2.4282
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of presentation of breast cancer in Missan's women

Abstract: The purpose of the study is to study the pattern of presentation of breast cancer in Missan's women regarding clinical, histopathological and immunological features of malignant breast tissue and focusing on the common presenting pattern and compare it to the neighboring area results. Across sectional study was done. The period of data collection extended from August 2013 to of March 2014. Eighty and five women were involved in the study which was conducted at AlShafaa Oncology Center in Missan province. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The current study shows that , The majority of the patients were in stage II (63 percent), followed by stage III (23 percent), stage IV(9%), and stage I (5%).The main histological type was invasive ductal carcinoma 93%,while invasive lobular carcinoma only (7%).This agrees with A research in the Maysan province in Iraq which shows that stage II was the most common(52.9%), followed by stage III(29.4%), indicating that the majority of the patients had late stage disease [31]. It also agrees with study in Iraq which shows Stage III cancer was found in 42.9 percent of the patients, whereas stage IV cancer was found in 25% of the patients and Invasive ductal carcinoma was the most frequent histopathologic type(81.4%), followed by invasive lobular carcinoma (6.9 % ) [19].…”
Section: Discussionsupporting
confidence: 85%
“…The current study shows that , The majority of the patients were in stage II (63 percent), followed by stage III (23 percent), stage IV(9%), and stage I (5%).The main histological type was invasive ductal carcinoma 93%,while invasive lobular carcinoma only (7%).This agrees with A research in the Maysan province in Iraq which shows that stage II was the most common(52.9%), followed by stage III(29.4%), indicating that the majority of the patients had late stage disease [31]. It also agrees with study in Iraq which shows Stage III cancer was found in 42.9 percent of the patients, whereas stage IV cancer was found in 25% of the patients and Invasive ductal carcinoma was the most frequent histopathologic type(81.4%), followed by invasive lobular carcinoma (6.9 % ) [19].…”
Section: Discussionsupporting
confidence: 85%
“…In a recent study published in 2018, 16 50.5% of patients had tumor stage III or IV. A study conducted in Maysan governorate in southern Iraq showed that stage II was the most common (52.9%) followed by stage III (29.4%), which also indicates that most of the patients presented with advanced-stage disease 17 . Another study 18 conducted in 2010 in the Northern region of Nigeria included 103 patients and showed that most (62%) presented with advanced-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the study carried out by Mutar et al in Iraq, it was reported that 42.9% of the patients were diagnosed with stage III and 25% with stage IV cancer, which are considered late stages [19] . In another study conducted in Maysan governorate in southern Iraq, most of the patients (82.3%) presented with advancedstage disease, stages II and III [35] . Late presentation was also found in another Iraqi study [36] , in which 47% of the patients presented with advanced stages of the disease and only 9.8% presented with stage I.…”
Section: Discussionmentioning
confidence: 93%